Comparative study of radium and strontium behaviour in contact with cementitious materials. (November 2020) - Kittnerová, Jana; Drtinová, Barbora; Štamberg, Karel; Vopálka, Dušan; Evans, Nicholas; Deissmann, Guido; Lange, Steve
Abstract: A comparative study of the sorption behaviour of radium and strontium was performed on various cementitious materials including crushed hardened cement pastes (HCP) and concretes as well as a synthesised calcium silicate hydrate (CSH) phase. R d values obtained for the Ra and Sr uptake on commercial cement materials were in the range of 50–380 L kg −1 and 10–30 L kg −1, respectively. No significant difference between the distribution ratios of the isotopes 226 Ra and 223 Ra was observed in the studied liquid to solid (L/S) ratio range, although different isotherms were determined. The R d values for Ra were found to increase with increasing L/S ratio. The cause of this effect is obviously the non-linearity of the sorption isotherm, here of the convex type. In contrast, Sr uptake seemed to be largely unaffected by variation of L/S ratios; this indicates an isotherm of almost linear type. Sorption experiments with the CSH phase confirmed the distinctive differences in the sorption behaviour between Ra and Sr as expected, with R d values significantly higher for Ra. Similarly, the difference between real cementitious materials and the pure CSH phase was confirmed, indicating that the sorption of alkaline earth elements is mainly due to uptake by CSH. The kinetics of Ra and Sr uptake on cementitious materials were evaluated by a set of models describing the sorption in heterogeneous systems based on different rate-controlling processes. The FD (film diffusion) model in the case of Ra, and the ID (diffusion in inert layer) model in the case of Sr provided the best fits. The influence of temperature on the kinetics of radium sorption was studied, suggesting change in the shape of isotherm with increasing temperature. Evaluation of sorption kinetic data yielded values of the apparent activation energy of the uptake process. Complementary through diffusion experiments using compacted crushed HCP confirmed and extended the findings obtained by evaluation of the batch sorption experiments performed with Ra and Sr. Highlights: Comparison of R d values of Ra and Sr sorption on different cementitious materials at different temperatures. Evaluation of possible sorption mechanisms. Sorption isotherm character for Ra at two significantly different concentrations. Control processes of Ra sorption based on kinetic models. Estimation of apparent activation energy of Ra sorption.